Complex field survey of the Tyatinskiy part of the “Kurilskiy” state nature reserve, Kunashir island, Kuril islands - Mikhail Yu. Grishchenko; Anna S. Murman; Igor E. Tamarovskiy; Darya A. Terekhova; Elizaveta M. Satosina; Veronika V. Shelukho; Anton S. Avchyan; Nikolay V. Ushakov (RUDN Journal of Ecology and Life Safety, 2023)
The study describes the results of field expeditionary research conducted by the authors on the territory of the Tyatinskiy cluster of the “Kurilskiy” state nature reserve (Kunashir island, the Great Kuril Ridge). The nature of the island is distinguished by its bright originality and is interesting for research both from the point of view of increasing the tourist, recreational and education attractiveness, and from the point of view of the implementation of environmental activities. During the research, a study of soils, vegetation cover and some climatic characteristics of the territory was carried out. It was revealed that the soils of the study area are mainly soils that combine the features of brown soils and volcanic soils; local plant communities are represented mainly by dark coniferous forests with a rich and varied admixture of broad-leaved species in the forest stand, the absence of pronounced undergrowth, a diverse grass-shrub canopy and a well-developed moss-lichen layer.